Daya Terima Puding Dadih Susu Kerbau (Bubalus Bubalis) dengan Penambahan Ekstrak Buah Strawberry (Fragaria Spp) - Mincu Manalu; Syalom Margareth Munthe (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
Local food refers to food ingredients that are produced or easily obtained within the community, one of which is buffalo milk dadih from North Sumatra, a traditional Batak dish that is rich in nutrients and has a tofu-like shape with a characteristic white color. This study aims to determine consumer acceptance of Buffalo Milk Dadih Pudding (Bubalus bubalis) combined with strawberry fruit extract (Fragaria spp.), where the processing and acceptance testing were conducted at the Food Technology Laboratory of Poltekkes Kemenkes Medan, Nutrition Department in Lubuk Pakam. This research is experimental with a completely randomized design that includes three treatments and two replications: Treatment A consists of 100 grams of buffalo milk dadih and 60 ml of strawberry extract, Treatment B consists of 100 grams of dadih and 80 ml of extract, and Treatment C consists of 100 grams of dadih and 100 ml of extract. Data were analyzed using ANOVA at α 5%, followed by Duncan's test. The results showed that the Buffalo Milk Dadih Pudding most favored by the panelists, based on color, texture, taste, and aroma, was Treatment C, which consisted of 100 grams of buffalo milk dadih and 100 ml of strawberry fruit extract.